Preeclampsia: nuevas etiologías - Chávez Dulce, Gerardo Rafael; Tejada Córdoba, Ángela Patricia; Suárez Ayala, Diana Vanessa; Gómez Cabrera, Fleider Leovani; Cabrera Fierro, Juan Sebastián; Figueroa, Claudia (Universidad y Salud, 2010)
Preeclampsia affects between 5% and 7% of all pregnancies and remains a major cause of maternal and perinatal mortality and morbidity, and it is particularly devastating in developing countries. The etiology of preeclampsia is unknown. At present, 4 hypotheses are the subject of extensive investigation, as follows: (1) Dysfunction of placental perfusion with increased angiogenic and biochemical factors, (2) Metabolic disorders related to the increase in adipokinas, (3) Inadequate immune adaptation and (4) Genetic factors related to the expression of genes involved in this pathology